Gastronomy and Tourism: Socioeconomic and Territorial Implications in Santiago de Compostela-Galiza (NW Spain) - Carral, Emilio V.; Río, Marisa del; López Pena, Zósimo (International Journal of Environmental Research and Public Health, 2021)
It is a worldwide well-known fact that gastronomic tourism does not always contribute to the cultural, social, economic, and territorial development of the host community. Therefore, its study requires a multidisciplinary and holistic approach to explore and interpret this phenomenon. From this perspective, the paper analyses the consumption of food products by tourists in Santiago de Compostela in Spain (2013–2014). Personal interviews (2081) with visitors and food industry establishment representatives were done. Compared with the normal food consumption of the Galician population, the food production capacity established by the corresponding Santiago foodshed calculation, and with the gastronomy official advertising (tourism web pages analysed by multimodal analysis), the gastronomic tourist experience is standardized and poor, limited to practically two products: rice with lobster, and octopus. This standardization supposes a high reduction in the diversity of the product that can be offered and produced in terms of proximity, and its territorial differentiation, comparing to the usual consumption of the Galician population, to the potential agricultural production by associated foodshed, and to the gastronomic advertising through official web pages. Thus, in this case, gastronomic tourism is not contributing to the social, economic, and territorial development of the host community or, ultimately, to the sustainability of tourism.
Keywords: gastronomy; tourism; food demand; restaurant offering; normal food consumption; official gastronomic advertisement; foodshed implication; Santiago de Compostela; Galiza (Spain); JCR; Scopus